Performance Analysis of On-Grid Rooftop Solar Power Plant with 600 Wp Capacity Based on Data Logger - I Made Ari Nrartha; Aldi Aryanugraha Mahendra; Sultan Sultan; I Made Ginarsa; Agung Budi Muljono; Sabar Nababan; Abdullah Zainuddin; Arnawan Hasibuan (Journal of Renewable Energy, Electrical, and Computer Engineering, 2024)
One of the renewable energy power plants whose construction is very massive is the solar power plant (PLTS) because it can be built anywhere in Indonesia. The type of PLTS with cheap investment is the on-grid system. This study aims to analyze the performance of the 600 Wp on-grid PLTS based on data loggers. Data logger is a data recording system designed using an Arduino Nano microcontroller equipped with sensors such as a solar radiation sensor (PYR20), temperature and humidity sensor (DHT22), PV module temperature sensor (DS18B20), DC voltage sensor, DC current sensor (ACS712), real time clock (DS3231), AC digital wattmeter module (PZEM-004T 10 A) and Micro SD Card Mini to store measurement data. The data logger is set to store measurement data every 5 minutes. The results of sensor measurements after calibration have an average measurement error of 5.20%, 0.56%, and 0.68% for the PYR20 irradiance sensor, 50 V range DC voltage sensor, and DC current sensor (ACS712). Based on the results of data logger recording, the 600 Wp on-grid PLTS system has a PV module efficiency in the range of 2.45 - 19.2% with an average of 8.60%, and the inverter (smart microgrid inverter) has an average efficiency of 89.40%.